Pharmacologic Inhibition of Glutamate Dehydrogenase 1 Improves Functional Recovery of Neuromuscular Junctions and Muscle Function in Duchenne Muscular Dystrophy - Pereira-Nunes, Andreia; Ammarah, Ummi; Shang, Min; Charatsidou, Iris; Sharma, Himal; Pereira Sorroche, Bruna; Nobis, Max; Burg, Thibaut; Verschoren, Stijn; Relaix, Frédéric; Rotini, Alessio; Van Den Bosch, Ludo; et al. (The American journal of pathology, 2025)
Presynaptic terminals of neuromuscular junctions (NMJs) are sensitive to glutamate, which contributes to NMJ plasticity and synaptic neurotransmission. However, the effect of glutamate on neurotransmission and its pharmacologic modulation in muscle pathologies are understudied. In this study, the efficacy of pharmacologic blockade of glutamate dehydrogenase (GLUD)-1 was investigated in mdx mice, a model of Duchenne muscular dystrophy. The GLUD1 inhibitor R162 mitigated the malfunctioning of NMJs by enhancing glutamate release from muscle fibers and increasing its availability in the muscle interstitium. Glutamate binding to its N-methyl-d-aspartate receptor on the presynaptic bottom of NMJs resulted in the increased release of acetylcholine and functional recovery of the action potential and muscle contraction, ultimately improving muscle performance. Finally, the GLUD1 inhibitor did not affect the homeostatic control of NMJs and the behavior of either healthy or dystrophic mice. This study suggests a promising and feasible therapeutic approach, based on muscle glutamate exploitation, to treating Duchenne muscular dystrophy, an unmet need in the clinic.